Unique mechanical properties of nanostructured transparent MgAl(2)O(4) ceramics - Zhang, Jie (Springer, 2013)
Nanoindentation tests were performed on nanostructured transparent magnesium aluminate (MgAl(2)O(4)) ceramics to determine their mechanical properties. These tests were carried out on samples at different applied loads ranging from 300 to 9,000 μN. The elastic recovery for nanostructured transparent MgAl(2)O(4) ceramics at different applied loads was derived from the force-depth data. The results reveal a remarkable enhancement in plastic deformation as the applied load increases from 300 to 9,000 μN. After the nanoindetation tests, scanning probe microscope images show no cracking in nanostructured transparent MgAl(2)O(4) ceramics, which confirms the absence of any cracks and fractures around the indentation. Interestingly, the flow of the material along the edges of indent impressions is clearly presented, which is attributed to the dislocation introduced. High-resolution transmission electron microscopy observation indicates the presence of dislocations along the grain boundary, suggesting that the generation and interaction of dislocations play an important role in the plastic deformation of nanostructured transparent ceramics. Finally, the experimentally measured hardness and Young’s modulus, as derived from the load–displacement data, are as high as 31.7 and 314 GPa, respectively.